Towards a Sociocritical Theory of the Text (2017)
The analysis of intratextual microsemiotics allows for the observation of contradictions resulting from the historical gaps projected in literary texts, which in turn reproduce the contradictions present in social and ideological structures. In his model, Cros privileges an abstract intratextual space named  genotext, through which history and its contradictions are incorporated. The historical material invested in the genotext corresponds to the principal interests of a society in a given moment of history. This implies that in the text, the writer gives word, even if non-consciously, to a series of transindividual subjects that run through it. This is illustrated through the analysis of a fragment of the second volume of Guzmán de Alfarache , by Mateo Alemán (Sevilla, 1547 - México, 1614), edited in 1604.